First year university science and engineering students' understanding of plagiarism - Yeo, Shelley (Routledge, 2007)
This paper is a case study of first‐year science and engineering students’ understandings of plagiarism. Students were surveyed for their views on scenarios illustrating instances of plagiarism in the context of the academic work and assessment of science and engineering students. The aim was to explore their understandings of plagiarism and their judgement about the seriousness of each incident, and to shed light on the decisions they might make in response to such situations. The data indicated that although students could provide sound definitions of plagiarism, they did not always appreciate the scope of class‐based activity that constitutes plagiarism. Some examples of plagiarism were regarded as less serious than others, and in contradiction with the institution’s policy. Students also generally favoured more lenient penalties than provided for by policy. The purpose of the study was to ascertain first‐year students’ developmental needs in relation to academic honesty, plagiarism and appropriate acknowledgement of others’ work.